Data curious : applying agile analytics for better business decisions - Allchin, Carl; Nabelsi, Sarah (O'Reilly Media, 2023)
Data has been a missing part of most academic curriculums for a long time, and we're all being affected. During challenging times, creating a data-informed culture can help you pivot quickly or prevent expensive missteps. Developing a data curious organization will take advantage of the burgeoning data resources available as a result of increasing digitalization. With this book, author Carl Allchin shows today's business professionals how to become data empowered. These tech-savvy business professionals will learn data literacy fundamentals--from understanding the possibilities to asking the right questions. You'll discover how to make the right technology choices and avoid pitfalls that could put your career and company at risk. Discover what an agile, empowered, data-driven organization should look like Examine how to use data in new ways to help your business come to life Learn key terms and concepts around data management and analytics Understand the differences between spreadsheet analysis and a data analytics pipeline Get advice for working with data scientists and explore ways to mitigate the IT department's concerns.